On the distributional orthogonality of the general Pollaczek polynomials - Jairo A. Charris; Felix H. Soriano (International Journal of Mathematics and Mathematical Sciences)
A distributional representation of the moment functional of the general Pollaczek polynomials is established. This representation holds for a wider range of parameters than the representation by a positive measure.